Exploring the Legacy of the 1948 Arnhem Land Expedition - Thomas, Martin (ANU Press, 2011)
In 1948 a collection of scientists, anthropologists and photographers journeyed to northern Australia for a seven-month tour of research and discovery-now regarded as 'the last of the big expeditions'. The American-Australian Scientific Expedition to Arnhem Land was front-page news at the time, but 60 years later it is virtually unknown. This lapse into obscurity was due partly to the fraught politics of Australian anthropology and animus towards its leader, the Adelaide-based writer-photographer Charles Mountford. Promoted as a 'friendly mission' that would foster good relations between Australia and its most powerful wartime ally, the Expedition was sponsored by National Geographic, the Smithsonian Institution and the Australian Government. An unlikely cocktail of science, diplomacy and popular geography, the Arnhem Land Expedition put the Aboriginal cultures of the vast Arnhem Land reserve on an international stage.